Hydroxo-bridged active site of flavodiiron NO reductase revealed by NRVS and DFT - Filipe Folgosa; Vladimir Pelmenschikov; Giorgio Caserta; Matthias Keck; Christian Lorent; Konstantin Laun; Yoshitaka Yoda; Leland B. Gee; Martin Kaupp; Kenji Tamasaku; James A. Birrell; Ilya Sergueev; et al. (Proceedings of the National Academy of Sciences, 2026)
The use of oxygen and nitrate as terminal electron acceptors provides organisms with a huge amount of available energy but necessitates methods to detoxify reactive intermediates. The mechanisms of NO and O 2 detoxification in many organisms involve flavodiiron proteins (FDPs). Although the proteinaceous ligands that coordinate the diiron active site of these enzymes are well established, its exact coordination environment remains under debate due to conflicting interpretations of crystallographic and spectroscopic/theoretical studies. Using 57 Fe nuclear resonance vibrational spectroscopy (NRVS), complemented by Mössbauer spectroscopy and density functional theory, we elucidated the redox-linked structural changes in the FDP from Escherichia coli . The as-isolated diferric state is best described as a dihydroxo-bridged Fe(III)–(μOH − ) 2 –Fe(III) core, which upon reduction converts to a monohydroxo Fe(II)–(μOH − )–Fe(II) center through the loss of one bridging ligand. This ligand rearrangement defines the structural basis for redox-linked reactivity in FDPs. The study further demonstrates that photoreduction of a stable metalloprotein species can occur under NRVS conditions, indicating that synchrotron-based vibrational measurements may induce subtle redox changes even under low photon flux. These findings provide a mechanistic framework for interpreting redox-linked ligand dynamics in diiron enzymes and highlight the need to collect damage-free X-ray crystal structures avoiding potential beam-induced reduction. Furthermore, diiron active sites are found in numerous other enzyme classes (e.g., methane monooxygenase), and therefore, our findings have implications way beyond the FDPs.